2016
DOI: 10.5194/acp-16-7317-2016
|View full text |Cite
|
Sign up to set email alerts
|

Simulated 2050 aviation radiative forcing from contrails and aerosols

Abstract: Abstract. The radiative forcing from aviation-induced cloudiness is investigated by using the Community Atmosphere Model Version 5 (CAM5) in the present (2006) and the future (through 2050). Global flight distance is projected to increase by a factor of 4 between 2006 and 2050. However, simulated contrail cirrus radiative forcing in 2050 can reach 87 mW m −2 , an increase by a factor of 7 from 2006, and thus does not scale linearly with fuel emission mass. This is due to non-uniform regional increase in air tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
3
21
3
1
Order By: Relevance
“…Asterisks mark extrapolated values calculated with the factor resulting from the radiative forcing in 2006 associated with air traffic volume using slant distance and track distance (Bock and Burkhardt, 2016b Pathway 6.0; RCP6.0.) (Chen et al, 2012). The radiation scheme is called every half hour calculating radiative transfer with and without contrail cirrus (see Bock and Burkhardt, 2016b, for details).…”
Section: Simulation Setupmentioning
confidence: 99%
“…Asterisks mark extrapolated values calculated with the factor resulting from the radiative forcing in 2006 associated with air traffic volume using slant distance and track distance (Bock and Burkhardt, 2016b Pathway 6.0; RCP6.0.) (Chen et al, 2012). The radiation scheme is called every half hour calculating radiative transfer with and without contrail cirrus (see Bock and Burkhardt, 2016b, for details).…”
Section: Simulation Setupmentioning
confidence: 99%
“…An explanation of this pattern requires a more detailed study. Such a study should include different absorption by optically thin clouds with different particle sizes (Inoue, 1985), wind-driven or convective uplift possibly causing pileus clouds (Garrett et al, 2006), presence of nitric acid, which has an 11 µm absorption band (Chepfer et al, 2007), the satellite viewing angles, and threedimensional radiation transfer. Figure 16.…”
Section: Noaa-avhrr Satellite Observations Above Hectormentioning
confidence: 99%
“…The long-term climate impact is mainly driven by CO 2 emissions. Modelling studies have shown that the direct radiative forcing from aviation is expected to represent 3-4 % (50-60 mW m −2 ) of the anthropogenic forcing (Lee et al, 2010;De León et al, 2012) and could reach 87 mW m −2 in 2025 (Chen and Gettelman, 2016). Aircraft-induced cloudiness also has an important impact on climate, although the quantitative assessment 9804 A.…”
Section: Introductionmentioning
confidence: 99%